Resilient MSMEs in the digital era: managing environmental uncertainty through dynamic capabilities - Ahmad Ahsin Kusuma Mawardi; Lilik Farida; Tatok Endhiarto; Tria Apriliana (BISMA (Bisnis dan Manajemen), 2025)
Business resilience is crucial for MSMEs to face post-pandemic challenges such as regulatory changes and economic fluctuations. Dynamic capabilities and digital transformation enable adaptation and innovation, enhancing competitiveness and sustainability, although there is still a lack of in-depth research on this relationship. This study aims to analyse the influence of environmental uncertainty on business resilience and MSME performance with dynamic capabilities and digital transformation as mediators, as well as business age as a moderating variable. This study uses primary data distributed through questionnaires with purposive sampling to 210 respondents who are MSMEs in Indonesia. Data analysis was conducted using SEM-PLS. The results of the analysis show that environmental uncertainty significantly affects dynamic capabilities, digital transformation, and business resilience, with positive coefficients for all three and a p-value below 0.05. Dynamic capabilities also have a positive impact on digital transformation and business resilience. However, dynamic capabilities do not have a significant effect on MSME performance. Both digital transformation and business resilience have a positive effect on MSME performance. In addition, dynamic capabilities moderate the influence of environmental uncertainty on digital transformation, while uncertainty through dynamic capabilities and digital transformation has a positive impact on business resilience and MSME performance. Business age does not moderate the influence of dynamic capabilities on business resilience.